Implementation of a Meliponario at Finca Las Dos Palmas in Florencia -Caquetá (Revista Sistemas de Producción Agroecológicos, 2021)
Beekeeping is a millenary agricultural tradition that consists of housing a swarm of bees in hives, obtaining from them honey and other natural products such as propolis, pollen, royal jelly and medicines, and at the same time it is friendly to the environment, since it allows the conservation of different plant species, protecting the biodiversity of a particular region or area. In Colombia the Productive Chain of Bees and Apiculture (CPAA) reports that honey is not seen competitively in the country's agricultural sector, despite the fact that it is carried out by public and private institutions, cooperatives, companies and associations. Stingless bees or meliponas are native to the American continent and typical of tropical and subtropical areas, of which more than 350 species have been identified, among which some produce high quality honey and serve as pollinators for the flowers of numerous species, in native forests and agricultural fields. Currently these bees are threatened by the destruction of native forests caused by the expansion of agriculture and livestock, by the damage caused by people who do not know about their brood, the way to obtain their honey and therefore destroy entire colonies. This work shows how to implement a simple meliponiculture system offering within the same job opportunities, consolidate knowledge about melipon bees for their conservation and research and generation of income from the sale of natural products, ecological conservation, healthy food and medicinal alternatives.
Keywords: Bees; beekeeping; meliponas; honey; meliponario